The Complementary Roles of Information and Communication Technology in Bangladesh Agriculture - Kashem, MA; Faroque, MAA; Ahmed, GMF; Bilkas, SE (Journal of Science Foundation, 2013)
Agriculture is the important sector and key contributors to the national GDP of Bangladesh. Around 20.60% of the total GDP of the country comes from the agricultural sector. But, most of the farmers of Bangladesh are still in lack of modern agricultural knowledge. Farmers need to access ICT and take information of agriculture and others which put them in better position in economic activities. So, it is very important to provide the farmers with the modern ICT facilities as soon as possible. This paper also provides a present status of ICT in agriculture for the potential users (policy makers, researchers, teachers and students, and other activists) of agricultural information to work cooperatively. In this paper gives a concept of database that may be applied to provide agricultural information in the effective way in digitally divided geographical areas using Location Based Services. Proposed system will assist the govt. to provide services & accessibility of proper digital contents not only the farmers but also the researchers and other people who are interested in this sector. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14639 J. Sci. Foundation, 8(1&2): 161-169, June-December 2010